Anthraquinones with potential antiproliferative activities from the fruits of Morinda citrifolia. Issue 9 (3rd May 2023) - Shen, Zhang-Yang; Zhao, Ying-Ying; Qiao, Ze-Hua; Xie, Zhen; Guan, Ruo-Qing; Liu, Ze-Yu; Liu, Yan-Ping; Chen, Guang-Ying; Fu, Yan-Hui
Abstract: The phytochemical investigation on the fruits of Morinda citrifolia led to the isolation and characterization of a new anthraquinone, moricitrifone (1 ), along with seven known anthraquinones (2 –8 ). The chemical structure of 1 was elucidated by extensive spectral analyses. The known compounds (2 –8 ) were identified by comparing their spectral data with those reported in the literature. The antiproliferative activities of all isolated anthraquinones (1 –8 ) against five human cancer cell lines: HL-60, SMMC-7721, A-549, MCF-7 and SW480 were evaluated in vitro . Compounds 1 –8 exhibited remarkable antiproliferative activities with IC50 values ranging from 0.26 ± 0.05 to 16.58 ± 0.18 μM, which were comparable to those of doxorubicin. Graphical Abstract: UF0001